2022
DOI: 10.1097/ju.0000000000002168
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal Multiparametric Magnetic Resonance Imaging–Ultrasound Fusion Targeted Prostate Biopsy Combined with Standard Template Improves Prostate Cancer Detection

Abstract: Purpose: Transperineal (TP) prostate biopsy provides an effective approach to prostate cancer (PCa) detection. Although transrectal targeted biopsy has been well described, the specific advantage of the standard TP template or TP targeted biopsy using multiparametric (mp) magnetic resonance imaging (MRI)ultrasound (US) fusion remains less understood and without consensus. Materials and Methods: We identified all men who underwent a transperineal standard 20-core template in addition to a targeted biopsy with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Of these, 17 (18%) met inclusion criteria and underwent full‐text analysis (Figure S1 ). One study 24 was excluded from the pooled analysis of CDRs due to overlapping patients with a subsequently published report 13 that included a larger sample size. However, only the earlier of the two reports included data on procedural complications and so was included in our analysis of this endpoint.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 17 (18%) met inclusion criteria and underwent full‐text analysis (Figure S1 ). One study 24 was excluded from the pooled analysis of CDRs due to overlapping patients with a subsequently published report 13 that included a larger sample size. However, only the earlier of the two reports included data on procedural complications and so was included in our analysis of this endpoint.…”
Section: Resultsmentioning
confidence: 99%
“…In two studies, 12–14% of clinically significant cancers that were missed on targeted biopsy were detected on systematic sampling of the prostate 20,21 . Further support for performing systematic biopsies comes from a study by Kim et al, in which up to 18.2% of cancers detected on targeted biopsy were upgraded on systematic biopsy 13 . Although some reports found that targeted biopsies alone were sufficient to detect clinically significant disease using the transperineal approach, this may be due to sampling of fewer systematic cores contributing to decreased sensitivity 36,37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Although in the past decade, multiparametric MRI has positioned itself in the assessment of prostate cancer, it mainly secures the identification of the index tumor, whereas less clinically (in)significant tumors can still be missed. 3,4 Hence, also template biopsies have obvious limitations and also may still miss smaller-sized tumors, 5,6 although global guidelines still include template biopsies in the assessment to select patients for focal therapy. 7…”
mentioning
confidence: 99%